The Impact of Digital Transformation Job Autonomy on Lawyers’ Support for Law Firms’ Digital Initiatives: The Mediating Role of Cognitive Adjustment and the Moderating Effect of Leaders’ Empathy - Bowei Liu; Shuang Cheng; Qiwei Zhou; Xueting Shi (Administrative Sciences, 2025)
Digital transformation has reshaped knowledge creation patterns, business models, and practices within the legal industry. However, many organizations have struggled to realize the anticipated benefits of digital transformation due to individual adaptation barriers. Drawing on the Job Demands–Resources model, this study employs both regression analysis and fuzzy-set qualitative comparative analysis (fsQCA) to investigate the mechanisms and the boundary conditions through which digital transformation job autonomy affects lawyers’ supportive behaviors toward digital change in law firms. The regression analysis of multi-wave survey data from 423 lawyers demonstrates that digital transformation job autonomy not only has a direct positive effect on lawyers’ digital transformation-supportive behaviors, but also indirectly promotes such behaviors through lawyers’ cognitive adjustment in the workplace. Furthermore, leader empathy enhances the relationship between digital transformation job autonomy and supportive behaviors. The fsQCA results identify multiple pathways leading to high and low levels of digital transformation-supportive behaviors among lawyers. These findings contribute to a deeper understanding of how organizations foster individual support for digital transformation.